An all-in-one self-healable capacitor with superior performance. Issue 6 (29th January 2018) - Liu, Fatang; Wang, Jingchen; Pan, Qinmin
Abstract : A supercapacitor achieved by in situ integrating electroactive components into a single network exhibits superior capacitive properties after 10 breaking/healing cycles. Abstract : Excellent self-healability is considered as a critical element for next-generation flexible/wearable energy-storage devices. However, realizing superior electrochemical performances remains a big challenge for such devices because self-healability intrinsically offsets their basic energy-storage functions. Here we demonstrate that the conflict can be effectively addressed for a supercapacitor via rationally designing its device configuration at a molecular level. The capacitor is fabricated by in situ integrating polyaniline (PANI) and H2 SO4 solution into a single network comprising the copolymer of vinylimidazole and hydroxypropyl acrylate (PVH). The all-in-one configuration combines fast charge-carrier transportation, good structural durability and excellent self-healability. Consequently, the resulting capacitor delivers a high specific areal capacitance and rate capability superior to its counterparts, but also maintains ultra-long cycling life even after breaking/healing 10 times. This example of configuration engineering offers a new and promising avenue to design self-healable energy-storage devices with outstanding performances.